Organizational Factors in Implementation of Patient Safety Culture in Hospitals: Systematic Literature Review - Darma, Septin Srimentari Lely; Purwaningsih, Purwaningsih; Ulfiana, Elida (Fundamental and Management Nursing Journal, 2021)
Introduction: Patient safety culture is a program organized to minimize the risk of unexpected events and improve patient safety. This study is aimed to explain the relationship between organizational factors in the implementation of patient safety culture in hospitals based on empirical studies in the last five years.Method: ProQuest, ScienceDirect, Sage, CINAHL, and google scholar databases have been searched using indexed keywords in the Medical Subject Heading (MeSH) on 2015-2020. JBI's review with a cross-sectional study design used to assess research quality. The PRISMA flowchart was used to summarize the study selection process in the literature review with inclusion and exclusion criteria adjusted to the PICOS framework.Results: We found 13 journals that consist of three studies discuss about leadership, seven journals describe about resources, and three journals relate to organizational structure.  Every country has a different characteristic in implementation of patient safety culture. The thirteen journals came from countries that divided in to three continents, there are Asia, Europe, and Africa. The results of this studyshow that leadership, resources, and, organizational structure can optimize the application of patient safety culture. Leadership support motivates health workers in the room in implementing a patient safety culture. Adequate resources reduce the risk of accidents at work, and an effective organizational structure creates good and conducive performance.Conclusions: Provide between three and five key words in alphabetical order, which accurately identify the paper's subject, purpose, method and focus. Don't use words or terms in the title as keywords. These keywords will be used for indexing purposes. Keywords cannot be more than 5 words or phrases in alphabetical order